In vitro evaluation of the antibacterial effects of MTA- Fillapex and BIO-C® sealer at different time intervals: Antibacterial effects of MTA- Fillapex and BIO-C® sealer - Raouf, Saya Hadi; Bakr, Diyar Khalid; Ahmed, Urfa Muneer; Amin, Bassam Karem (Cellular and Molecular Biology, 2023)
Failure of endodontic treatment is closely associated with bacterial infection, the study aimed to evaluate the antibacterial properties of MTA- Fillapex and BIO-C against two bacterial species Enterococcus faecalis (E. faecalis) and Staphylococcus aureus (S. aureus). In this in vitro study, two endodontic sealers were used to evaluate antibacterial properties by using an agar diffusion test (ADT) and direct contact test (DCT). The width of the growth inhibition zone after 24 hours was reported in (ADT) as the endodontic sealers’ effectiveness. In DCT, the survival of microorganisms was assessed at various periods following the exposure of the bacterial suspension to the sealers for (20 and 40 min) at (1 day, 7 days and 14 days). Colony-forming unit (CFU) counts were made. In ADT, the zones of microbial growth inhibition in BIO-C sealer caused by E. Facealis were relatively larger than that created due to S. Auerous bacteria with mean 0.781 mm and 0.538 mm respectively. Thus, this difference turned out to be significant (p<0.001). In DCT At both time points tested, no significant difference was found among control cases against the tested microbes (p > 0.05). In terms of sealers, BIO-C had the most potent antimicrobial properties. It showed significant inhibition against both E.faecalis and S. Auerous on day 1 and the first week of contact times tested. Moreover both BIO-C and MTA Fillapex sealers perform worthy antibacterial activity up to 1 week and BIO-C sealers show better antibacterial efficacy against E. faecalis than MTA Fillapex sealers.